2006
DOI: 10.1124/mol.106.024703
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Cyclized Quinones Derived from Dopamine, DOPA, and 3,4-Dihydroxyphenylacetic Acid in Proteasomal Inhibition

Abstract: We examined the ability of oxidation products of dopamine, DOPA, and 3,4-dihydroxyphenylacetic acid (DOPAC) to inhibit proteasomal activity. Dopamine, DOPA, and DOPAC underwent tyrosinase-catalyzed oxidation to generate aminochrome, dopachrome, and furanoquinone, respectively. In these studies, the oxidation of dopamine by tyrosinase generated product(s) that inhibited the proteasome, and proteasomal inhibition correlated with the presence of the UV-visible spectrum of aminochrome. The addition of superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 43 publications
3
66
2
Order By: Relevance
“…Aminochrome also induces protein degradation dysfunction by: i) impairing the proteasomal system in different in vitro models (Xiong et al, 2014; Zafar et al, 2006; Zhou and Lim, 2009); ii) inhibiting autophagy by preventing the adequate formation of microtubules required for the fusion of autophagic vacuoles and lysosomes in rat and human cell lines (Huenchuguala et al, 2014; Muñoz et al, 2012a; Paris et al, 2010); iii) inducing lysosomal dysfunction in human cell lines by affecting lysosomal acidification required for protein degradation inside these organelles (Huenchuguala et al, 2014). Aminochrome can induce oxidative stress when it is one-electron reduced by flavoenzymes to leukoaminochrome- o -semiquinone radical, which is extremely reactive with oxygen and auto-oxidizes immediately to aminochrome generating a redox cycling between aminochrome and leukoaminochrome- o -semiquinone radical, depleting both NADH or NADPH and oxygen, the latter being reduced to superoxide radical with consequent formation of hydroxyl radical, as demonstrated in rat cell lines experiments (Arriagada et al, 2004).…”
Section: Iron In Da Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminochrome also induces protein degradation dysfunction by: i) impairing the proteasomal system in different in vitro models (Xiong et al, 2014; Zafar et al, 2006; Zhou and Lim, 2009); ii) inhibiting autophagy by preventing the adequate formation of microtubules required for the fusion of autophagic vacuoles and lysosomes in rat and human cell lines (Huenchuguala et al, 2014; Muñoz et al, 2012a; Paris et al, 2010); iii) inducing lysosomal dysfunction in human cell lines by affecting lysosomal acidification required for protein degradation inside these organelles (Huenchuguala et al, 2014). Aminochrome can induce oxidative stress when it is one-electron reduced by flavoenzymes to leukoaminochrome- o -semiquinone radical, which is extremely reactive with oxygen and auto-oxidizes immediately to aminochrome generating a redox cycling between aminochrome and leukoaminochrome- o -semiquinone radical, depleting both NADH or NADPH and oxygen, the latter being reduced to superoxide radical with consequent formation of hydroxyl radical, as demonstrated in rat cell lines experiments (Arriagada et al, 2004).…”
Section: Iron In Da Oxidationmentioning
confidence: 99%
“…Interestingly, the products of DA oxidation (DA- o -quinone, aminochrome and 5,6-indolequinone) are directly involved in mitochondria dysfunction, protein degradation alteration, α-synuclein aggregation to neurotoxic oligomers and oxidative stress in dopaminergic neurons (Fig. 1, 2), suggesting that these o -quinones can play an important role in the degenerative process, resulting in the loss of SN dopaminergic neurons containing NM (Aguirre et al, 2012; Arriagada et al, 2004; Bisaglia et al, 2007; Dibenedetto et al, 2013; Hauser and Hastings, 2013; Huenchuguala et al, 2014; LaVoie et al, 2005; Martinez-Vicente et al, 2008; Muñoz et al, 2012a, 2015; Norris et al, 2005; Paris et al, 2010; Van Laar et al, 2009; Whitehead et al, 2001; Xiong et al, 2014; Xu et al, 1998; Zafar et al, 2006; Zhou and Lim, 2009). …”
Section: Role Of Da Oxidation In Neurodegenerative Processes Of Pdmentioning
confidence: 99%
“…In a related work, DA was found to induce proteasome inhibition in PC12 cells, and this inhibition was attenuated by glutathione, MAO inhibitors, or a DA uptake inhibitor [22]. In addition, Zafar et al have demonstrated that DA quinone has the ability to inhibit proteasomal activity [13]. These findings suggest a possible role of proteasome inhibition in the toxicity induced by high levels of DA or its quinone in the cytosol.…”
Section: Da Quinone Formation As Dopaminergic Neuron-specific Oxidatimentioning
confidence: 95%
“…In our previous reports, it has been shown that quinone formation plays an important role in a model of Parkinson's disease [8] and in methamphetamine (METH)-induced dopaminergic neurotoxicity [9]. Furthermore, several studies have clarified that the cytotoxicity of quinone formation is closely linked to other hypotheses of pathogenesis of Parkinson's disease and METH neurotoxicity such as mitochondrial dysfunction, inflammation and proteasome impairment [10][11][12][13]. Therefore, some molecules or reagents to prevent quinone formation or quench generated quinones would be potential therapeutic approaches against DA quinone-related dopaminergic neuronal disorders.…”
Section: Introductionmentioning
confidence: 97%
“…(iii) Protein degradation dysfunction in which dopamine oxidation inactivates the proteasome system, although it is not clear which of the o-quinones is responsible for this inactivation [53]. However, aminochrome has been reported to inactivate the proteasome [108,109]. Aminochrome forms adducts with α-and β-tubulin preventing the formation of microtubules required for autophagosome fusion with lysosomes and induces lysosome dysfunction by increasing its internal pH [58,59,110].…”
Section: Role Of Dopamine Ortho-quinones In Parkinson's Diseasementioning
confidence: 95%